One is: a reading of Plato's parmenides in respect of parmenides' poem - Akça, Ergün Ahmet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This dissertation offers a new analysis and evaluation of a part of Plato’s dialogue Parmenides, focussing on the hypothesis “one is” from the perspective of historical Parmenides’ poem or, more precisely the goddess’ muthos in the poem. This kind of reading shows that the context of the argumentation under the hypothesis “one is" in the dialogue is mainly determined by the restrictions laid out in the muthos of the goddess. The main thesis of the goddess’ muthos is “to be is,” which may be expressed as follows: only “is” is said of to be, and “is” is said of only to be. Following hints in the discussion of the hypothesis, it is revealed that the dialogue’s character Parmenides takes this restriction as a model, and extends it to any phusis and its proper subject of discourse: (i) only its proper nature is said of a subject of discourse, and (ii) a nature is said of only its proper subject. Such an approach shows that though the hypothesis “one is” is about the one in the dialogue, the real issue to be discussed under this hypothesis is about to be, and the conditions to say “is” to any subject of discourse. It is argued that in accord with these restrictions Plato’s character Parmenides begins the first deduction under the hypothesis “one is” with “the one one.” The main question of the deduction is how it can be argued that “the one is” follows from “the one one” under the restrictions about to be and the one. In the second deduction, following these restrictions, Parmenides takes to be as being different from the one, and obtain a whole that is composed of to be and the one. It is argued that the argumentation in this deduction is also valid for to be, and produces an aporia: to be is like and unlike. This discusion concludes that if we trust Parmenides’ argument in the dialogue, any subject which has phusis can in no way be if “to be is
Keywords: Socrates.; Zeno, of Elea.